Probiotics alleviate chronic ethanol exposure-induced anxiety-like behavior and hippocampal neuroinflammation in male mice through gut microbiota-derived extracellular vesicles - Jiaxin Pei; Chaoxu Zhang; Qian Zhang; Hao Yu; Huiya Yuan; Yufu Guo; Hui Shen; Hao Liu; Changliang Wang; Fanyue Meng; Chenyang Yu; Jinming Tie; et al. (Journal of Nanobiotechnology)
Abstract Background Probiotics can colonize both the human and animal bodies and consist of active microorganisms that are beneficial to health. The use of probiotics has been shown to alleviate certain neurological diseases and disturbances in gut microbiota resulting from chronic ethanol exposure. Research indicates that probiotics can influence the nervous system via the microbial-gut-brain axis, wherein extracellular vesicles secreted by the gut microbiota play a significant role in this process. Results In this study, we first established a 30-day ethanol exposure and probiotic gavage mouse model, both of which influenced behavior and the composition of gut microbiota. We then extracted gut microbiota-derived extracellular vesicles from the feces of these model mice and injected them into new mice via the tail vein to assess the role of each set of extracellular vesicles. The results indicated that the extracellular vesicles derived from the intestinal microbiota in the ethanol group induced anxiety-like behavior and hippocampal neuroinflammation in the recipient mice. In contrast, the extracellular vesicles secreted by the gut microbiota from the probiotic group mitigated the anxiety-like behavior and neuroinflammation induced by ethanol-influenced extracellular vesicles. Conclusions Our study demonstrates that extracellular vesicles secreted by the gut microbiota can influence the nervous system via the microbial-gut-brain axis. Furthermore, we found that the extracellular vesicles secreted by the gut microbiota from the probiotic group exert a beneficial therapeutic effect on anxiety and hippocampal neuroinflammation. Graphical Abstract